Human rights in the digital domain : core questions / edited by Tiina Pajuste. - Pajuste, Tiina (Cambridge University Press, 2026)
As digital technologies transform governance, communication, and public life, human rights frameworks must adapt to new challenges and opportunities. This book explores four fundamental questions: how digitalisation changes the application of human rights, how human rights law can respond to the challenges of digital technology, how freedom of expression applies online, and how vulnerable groups are affected by digitalisation. With contributions from leading scholars, the book combines legal analysis with insights from ethics, environmental education, and medical research. It examines critical topics such as AI regulation, platform accountability, privacy protections, and disinformation, offering an interdisciplinary and international perspective. By balancing different viewpoints, this book helps readers navigate the complexities of human rights in the digital age. It is an essential resource for anyone seeking to understand and shape the evolving landscape of digital rights and governance. This title is also available as open access on Cambridge Core.